2012
DOI: 10.1161/circep.112.975755
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Presentation of Externalized Conductors and Electrical Abnormalities in Riata Defibrillator Leads After Fluoroscopic Screening

Abstract: Background-The Riata family of implantable cardioverter-defibrillator (ICD) leads is prone to a specific insulation abrasion characterized by externalization of conductor cables. The objective of this study was to determine the prevalence of externalized conductors and electrical abnormalities in Riata ICD leads by fluoroscopic screening and standard ICD interrogation. Methods and Results-All ICD implantation centers were contacted by the Netherlands Heart Rhythm Association Device Advisory Committee to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 17 publications
1
41
1
1
Order By: Relevance
“…Prevalence of CE ranged from 11% to 43% ( Figure 2A). 6,[10][11][12][13][15][16][17][19][20][21][22]25 Based on random effects modeling, the overall rate of CE was 23.1% (95% CI 19.0%-27.6%). In most but not all of these 13 studies, an average lead dwell time was reported (range 3.5-6.2 years).…”
Section: Search Resultsmentioning
confidence: 99%
“…Prevalence of CE ranged from 11% to 43% ( Figure 2A). 6,[10][11][12][13][15][16][17][19][20][21][22]25 Based on random effects modeling, the overall rate of CE was 23.1% (95% CI 19.0%-27.6%). In most but not all of these 13 studies, an average lead dwell time was reported (range 3.5-6.2 years).…”
Section: Search Resultsmentioning
confidence: 99%
“…1 The lead is the weakest link in all ICD systems: multiple studies have shown failure rates ranging from 10% to 50% during long-term follow-up and smaller lead size may be a predictor of a higher failure rate. [2][3][4][5][6] Even with alerts based on absolute values of pacing impedance, the most common presentation of lead failure (LF) is inappropriate shocks [1][2][3][4] delivered in response to rapid oversensing of nonphysiological signals. To improve detection of LF compared with conventional impedance monitoring, the Lead Integrity Alert (LIA) 7,8 was developed, which is triggered by relative changes in impedance and evidence of transient, rapid oversensing.…”
mentioning
confidence: 99%
“…Cheung et al 5 reported on 314 patients and found a significantly higher rate of externalized conductors (57%) in failed leads than did other investigators. 5,[8][9][10] This difference may relate to implantation technique or dedicated surveillance at this single center that resulted in a greater proportion of externalization than seen in our study. Previous studies have examined venous approach, degree of slack in leads, lead placement in the pocket, and degree of curvature in the lead as it passes through the tricuspid valve as it relates to ICD fracture.…”
Section: Discussionmentioning
confidence: 72%